2014
DOI: 10.30638/eemj.2014.273
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of Nature: The Power of the Type of Visitors

Abstract: Nature tourism has a strong potential, and as a result of this tourism activity, the environmental concern is considered an important element which guides business and tourism activity. This element also generates the change in the society's behaviour, in order to conciliate economic and political interest with the environmental ones, with the final aim to guarantee the existence of these resources in the future and the tourism competitiveness of these natural areas. To get this purpose of sustainable developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 80 publications
11
17
0
Order By: Relevance
“…From the theoretical perspective, the present study establishes a similarity to the groups found by Cordente-Rodríguez et al (2014), who establish two segments that are referred to as group 1 "Los naturalistas", similar to the "ecotourists" of the present study and group 2 "multiple motivations", very similar to what was called "multi tourists" motivations" of the present investigation. However, in the Samanes recreation area there was a group called "Indifferent tourists" with average scores on the motivational variables, focusing this group of tourists visiting this area on other motivations not studied as part of ecotourism.…”
supporting
confidence: 83%
“…From the theoretical perspective, the present study establishes a similarity to the groups found by Cordente-Rodríguez et al (2014), who establish two segments that are referred to as group 1 "Los naturalistas", similar to the "ecotourists" of the present study and group 2 "multiple motivations", very similar to what was called "multi tourists" motivations" of the present investigation. However, in the Samanes recreation area there was a group called "Indifferent tourists" with average scores on the motivational variables, focusing this group of tourists visiting this area on other motivations not studied as part of ecotourism.…”
supporting
confidence: 83%
“…From the point of view of the demand, tourists have access to an ever-increasing number of proposals that include environmentally responsible experiences [13,14]. Moreover, in terms of the supply, there is not a lot of scientific literature, fundamentally caused by the small size of many of the companies operating in this sector.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed model was analysed by modelling structural equations using Partial Least Squares (PLS). This is one of the most used methodologies when the cause-effect relationships need to be analysed [7,64,65] since it informs us of the sign and intensity of these relationships. A PLS path model consists in two components.…”
Section: Methodsmentioning
confidence: 99%
“…This country has 15 National Parks that represent 0.76% of its territory. Likewise, this figure is the best known by society among all the protection categories and has a great tourist attraction, registering millions of visits annually [7,8]. Furthermore, Spanish National Parks represent exceptional environments with their own culture and biological personality, due to the authenticity of their resources, which is one of the country's distinguishing characteristics [9].…”
Section: Introductionmentioning
confidence: 99%